Renal transplantation in patients with abdominal aortic aneurysm--a new surgical approach - Adamec, Milos; Matia, Ivan; Janousek, Libor; Fronek, Jiri; Bachleda, Petr; Lácha, Jiri; Viklický, Ondrej (Transplant international, 2004)
An increasing number of abdominal aortic aneurysms occurs in renal failure patients because of an accelerated atherosclerosis process associated with uraemia. When technically feasible, endovascular repair of an abdominal aortic lesion should be considered as the treatment of choice. If a surgical repair is suggested, there are several options to select from. Since November 1999, we performed simultaneous aortic reconstruction using fresh arterial allograft and kidney transplantation in five uraemic patients with asymptomatic abdominal aortic aneurysm. The operative and postoperative course of four patients passed without major complications. One patient had ischaemic colitis early after the operation, which required a partial resection of the colon. One patient died 6 weeks after the operation due to non-vascular causes. In conclusion, the advantage of our single-phase procedure is that both diseases are treated simultaneously during a single hospital stay. Moreover, with our procedure, the risk of vascular graft infection in patients with chronic immunosuppression is low.
Keywords: aorta abdominalis; počítačová rentgenová tomografie; Vascular Surgical Procedures; Humans; Aorta, Thoracic; lidé středního věku; Aorta, Abdominal; Female; dospělí; angiografie; aneurysma břišní aorty; lidé; uremie; Aortic Aneurysm, Abdominal; Adult; aorta thoracica; transplantace ledvin; Angiography; ženské pohlaví; Male; výkony cévní chirurgie; Middle Aged; Tomography, X-Ray Computed; Kidney Transplantation; mužské pohlaví; Uremia